BIMBINGAN TEKNIS PENGGUNAAN MIKROSKOP UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS SANTRI DI PONDOK PESANTREN DARUL AZHAR ACEH TENGGARA - Adawiyah, Rabiyatul; Suriani, Halisah; Laksana, Akum (COVIT (Community Service of Tambusai), 2023)
This PKM technical guidance was carried out at the Darul Azhar Aceh Tenggara Islamic boarding school on Thursday, January 19 2023. All class VII students werw targeted and this activity was carried out using the ecplicit instruction method (direct teaching). Most of the students at the Darul Azhar Aceh Tenggara Islamic boarding svhol have a basic understanding of microscope increases significantly after the introduction and practice of microscopy. Only 20% of students in demonstrating being able to understand microscopy. After this activity was carried out there was an increase, namely 90% of class VII students were able to understand the use of a microscope. Keywords: technical guidance, microscopy, process skills, science